2013
DOI: 10.1007/s12028-013-9853-y
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Drainage for the Treatment of Severe Bacterial Meningitis

Abstract: In this study, the use of lumbar drainage in adult patients with severe bacterial meningitis was safe, and likely contributed to the low mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 21 publications
0
20
0
4
Order By: Relevance
“…brain swelling or hydrocephalus). Several multistep treatment strategies have been described to reduce intracranial pressure in observational studies [108][109][110] and have been suggested to improve outcome. However, no RCTs have been performed, and results varied considerably between observational studies.…”
Section: Grade Bmentioning
confidence: 99%
“…brain swelling or hydrocephalus). Several multistep treatment strategies have been described to reduce intracranial pressure in observational studies [108][109][110] and have been suggested to improve outcome. However, no RCTs have been performed, and results varied considerably between observational studies.…”
Section: Grade Bmentioning
confidence: 99%
“…ICP-targeting treatment of severe ABM has been reported with promising results [14][16], [23] but is not routinely used. [4], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate hyperventilation, osmotherapy and ICP-targeted treatment can be considered in critical cases of ABM [7], [22][24], and is well established in patients suffering from traumatic brain injury (TBI) [25]. A neurocritical care approach using ICP-targeted treatment with favorable results has been reported in three relatively small and uncontrolled studies of ABM-patients presenting high ICP and severe impairment of consciousness [14][16], and promising results have recently been reported in a cohort study using lumbar drainage [23]. However promising, there is a lack of evidence supporting ICP-guided treatment in ABM [7], [22].…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, another group showed that early use of CSF diversion by means of a lumbar drain led to improved results. 1 The use of invasive monitoring has previously been shown to be safe in the pediatric population with meningitis 28 and is considered a safe practice in other neurological emergencies in adult patients. Although parenchymal monitors are more popular, plausible results can be anticipated with early use of external ventricular drains, which allow both continuous ICP monitoring and ease of immediate CSF evacuation in susceptible patients.…”
Section: Clinical Relevancementioning
confidence: 99%